BUILDING PLANNING FOR THE MEDICAL BUILDING AT JENDERAL ACHMAD YANI UNIVERSITY BANDUNG USING SPECIAL MOMENT RESISTING FRAME SYSTEM - arif irfan maulana; chunyang zhu (Jurnal Online Skripsi Manajemen Rekayasa Konstruksi (JOS-MRK), 2025)
Indonesia, as a country prone to earthquakes, motivates civil engineers to prioritize earthquake-resistant structural planning. The primary goal is to ensure that buildings not only withstand seismic forces but also exhibit ductile behavior during strong earthquakes. National standards like SNI 2847-2013 and SNI 1726-2012 provide clear guidelines for using Special Moment Resisting Frame Systems (SMRFS) in designing earthquake-resistant buildings. The implementation of these standards is crucial to be disseminated among academics, consultants, and contractors to ensure that all planning aspects meet the established safety standards. The author conducted research to design Building Medical Building at Jenderal Achmad Yani University, Bandung, integrating SMRFS according to SNI 2847-2013 and SNI 1726-2012. The location of the building in Bandung, known for its high seismic activity, emphasizes the urgency of ensuring structural reliability, especially for high-rise buildings. The planning process involved using the ETABS application for comprehensive analysis of structural resilience against seismic moment forces. Pushover analysis was employed as a method to evaluate the structural performance under earthquake loads. This method not only measures the capacity of the structure to withstand push forces but also predicts failure patterns and plasticity distribution in structural elements. Thus, pushover analysis aids in identifying weak points that require improvement or reinforcement to ensure the structure can withstand and exhibit ductile behavior during strong earthquakes. Overall, this research aims to optimize structural designs to meet high earthquake resilience requirements in accordance with geographic conditions and national standards. The application of SMRFS and pushover analysis is expected to not only enhance the structural safety of laboratory buildings but also make a significant contribution to the development of safe and sustainable infrastructure in Indonesia.